Analysis of Study Habits and Their Relationship with Biology Learning Outcomes of Class XI MIPA Students at SMA N 8 Padang - Putri, Mifta Hayati; Hendri, Wince; Har, Erman; Gusmaweti, Gusmaweti (International Journal of Education and Teaching Zone, 2022)
This study aims to analyze study habits and their relationship with biology learning outcomes for students of class XI MIPA at SMA Negeri 8 Padang. This type of research is descriptive, with a total sample of 45 students in the odd semester of the 2021/2022 academic year. The sampling technique was simple random sampling using a questionnaire. The results showed that the highest average study habits were habits in student preparation (28.82 ± 3.36), reading textbooks (23.84 ± 3.05) making notes and summaries (24.15 ± 3.14 ) repeating lessons (17.06 ± 3.04) facing e xa ms (23.60 ± 2.94) and completing assignments (16.35 ± 2.02). Study habits contribute to students' biology learning outcomes with a t count of 2,794. The relationship between study habits and learning outcomes in general shows a low relationship (r = 0.161). Furthermore, the relationship between variable habits showed a low relationship between taking notes and summaries (r = 0.216), with study preparation (r = 0.174), reading habits of textbooks (r = 0.128), repeating lessons (r = 0.103), in facing exams ( r = 0.102) and the relationship between habits in completing tasks with learning outcomes (r = 0.000) is in the very low category. From this research, it can be concluded that the relationship between study habits and learning outcomes in taking notes and summaries with learning outcomes is in the low category, while the relationship between learning preparation habits, reading textbooks, repeating lessons, facing exa ms and the relationship between habits in completing assignments is in the very low category.